ECO-FRIENDLY PESANTREN: STRATEGI PENGELOLAAN SAMPAH BERBASIS KOMUNITAS MELALUI ECOBRICKS DAN ECO-ENZYME - Latifah, Sri; Suryani, Yani (Universitas Padjadjaran, 2025)
Waste management remains a major challenge in many Islamic boarding schools (pesantren), including Pesantren Irsyaadul Ibad in East Lampung, which accommodates over 700 students (santri). This program aims to educate the pesantren community on utilizing ecobricks and ecoenzymes as environmentally friendly waste management solutions. Using the Participatory Action Research (PAR) method, the program encompasses several stages: planning, training, implementation, observation, and reflection. Data collection was conducted through questionnaires to assess the program's effectiveness. The results indicate a significant improvement in the students’ environmental awareness and understanding after participating in the program. The santri demonstrated enhanced skills in waste management, particularly in repurposing plastic waste into functional ecobricks and processing organic waste into ecoenzymes. These improvements were achieved through interactive training sessions and hands-on activities that encouraged active participation at every stage of the program. Through the PAR approach, the program successfully produced valuable products, such as garden decorations made from ecobricks and ecoenzyme liquids for daily household use. Additionally, the program’s implementation resulted in a notable reduction in the volume of waste generated within the pesantren environment. Reflections from the activities highlighted the program’s positive impact, including a cleaner environment and the establishment of a pesantren community with a strong sense of awareness and commitment to sustainable waste management practices. This program model can be replicated in other pesantren as a tangible contribution to environmental sustainability.Pengelolaan sampah menjadi tantangan utama dibanyak pesantren, termasuk Pesantren Irsyaadul Ibad di Lampung Timur, yang dihuni oleh lebih dari 700 santri. Program ini bertujuan untuk mengedukasi warga pesantren dalam memanfaatkan ecobrick dan ecoenzyme sebagai solusi pengelolaan sampah yang ramah lingkungan. Dengan metode Participatory Action Research (PAR), kegiatan ini mencakup tahap perencanaan, pelatihan, implementasi, pengamatan, dan refleksi. Instrumen pengumpulan data yang digunakan yaitu angket untuk mengetahui keberhasilan program yang dilakukan. Hasil kegiatan menunjukkan adanya peningkatan signifikan dalam pemahaman dan kepedulian lingkungan santri setelah mengikuti program. Santri menjadi lebih terampil dalam mengelola sampah, memanfaatkan bahan bekas menjadi ecobrick yang berguna, serta mengolah limbah organik menjadi ecoenzyme. Peningkatan ini terjadi melalui proses pelatihan interaktif dan praktik langsung yang mendorong keterlibatan aktif para peserta dalam setiap tahap kegiatan. Melalui metode PAR, program ini berhasil menciptakan produk bernilai guna seperti hiasan taman dari ecobrick dan cairan ecoenzyme yang bermanfaat untuk kebutuhan sehari-hari. Implementasi program juga menunjukkan pengurangan signifikan jumlah limbah yang dihasilkan di lingkungan pesantren. Refleksi dari kegiatan ini menegaskan dampak positif berupa lingkungan yang lebih bersih, serta terbentuknya komunitas pesantren yang memiliki kesadaran dan komitmen tinggi terhadap pengelolaan sampah berkelanjutan. Model program ini dapat direplikasi di pesantren lain sebagai kontribusi nyata dalam menjaga keberlanjutan lingkungan